2017
DOI: 10.1037/ipp0000063
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Informant Ratings of Internalizing and Externalizing Behavior in Adolescent–Parent Pairs in Six Countries. Does Being Adopted Make a Difference?

Abstract: Low agreement between self report and parent report on the behavioral adjustment of adolescents has been widely documented in the literature. However, it has been little studied in connection with adoptees. In the current research, the magnitude of agreement between adolescents and their parents' reports of adolescents' behavioral problems and the direction of the possible discrepancies between these reports are studied. A comparison is made between adopted and non-adopted adolescent-parent dyads. The research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…The present study was limited to the use of parent reports of child internalising symptoms and externalising problems due to the young age of the children when placed for adoption, which precluded using teacher or child reports of difficulties. Whilst it has been suggested that adoptive parents may pay greater attention to their children’s adjustment than birth parents [17], a recent study refuted this [87]. However, we speculate that adoptive parents may be less able to accurately report on their child’s externalising problems and internalising symptoms early on in the child’s placement as parents are likely to be getting to know their children; this may account for the lack of association detected between ACEs and children’s externalising problems.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was limited to the use of parent reports of child internalising symptoms and externalising problems due to the young age of the children when placed for adoption, which precluded using teacher or child reports of difficulties. Whilst it has been suggested that adoptive parents may pay greater attention to their children’s adjustment than birth parents [17], a recent study refuted this [87]. However, we speculate that adoptive parents may be less able to accurately report on their child’s externalising problems and internalising symptoms early on in the child’s placement as parents are likely to be getting to know their children; this may account for the lack of association detected between ACEs and children’s externalising problems.…”
Section: Discussionmentioning
confidence: 99%
“…In the Chinese context, studies have shown that children and adolescents’ self-reported psychological distress scores were higher than those reported by their parents and teachers, indicating that adolescents tend to overestimate their own socioemotional problems (Roskam et al, 2017; Tepper et al, 2008). Of note, during early adolescence Chinese students are intensely involved in school assignments and activities, and teachers have more opportunities to observe their behavioral adjustment (Lan, Scrimin, & Moscardino, 2019).…”
Section: Self-reports and Teacher-reports Of Emotional-behavioral Promentioning
confidence: 99%
“…First, we aimed to investigate the association between perceived status-based discrimination and emotional-behavioral problems among Chinese rural-to-urban migrants in early adolescence from a cross-informant perspective involving both self-reports and teacher-reports of youth’s outcomes. Based on the literature reviewed above, we anticipated that higher levels of status-based discrimination would be associated with more emotional-behavioral problems, and that these associations would be stronger for self-reported than for teacher-reported outcomes due to adolescents’ tendency to overestimate their psychological difficulties (Roskam et al, 2017; Tepper et al, 2008).…”
Section: The Present Studymentioning
confidence: 99%
“…In a meta-analysis of 119 studies, a weak mean correlation was found between child- and parent-reports of overall emotional and behavioral problems in children and adolescents [ 30 ]. More recent work has confirmed these findings, similarly reporting low to moderate agreement across parent- and child-reports of child adjustment in both community [ 31 , 32 , 33 , 34 , 35 , 36 ] and clinical samples [ 37 , 38 , 39 , 40 ]. Interestingly, there is some research suggesting that parents may be better at reporting child externalizing problems, while children’s self-reports may reflect their own internalizing problems more accurately [ 33 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 77%